Analysis of the influence of organizational culture and organizational climate on job satisfaction - Rohmah Kurniawati; Waloyo Waloyo; Achmad Sholihin (Institute of Computer Science (IOCS), 2023)
Organizational culture is something that needs to be considered by assigning employees according to their workload and responsibilities. Employee treatment is equivalent to respect for employees where lack of appreciation will reduce employee job satisfaction. The problem is that job satisfaction and performance of employees of Tandes Subdistrict, Surabaya City are closely related to the livelihood of employees. The approach used in this study is a type of quantitative research, namely in data collection, research using quantitative methods where research is based on the philosophy of positivism. the size of the sample is determined as a whole from the total population so that the size of the sample in this study is 37 ASN employees (100%) in Tandes District, Surabaya City. In this study used multiple linear regression analysis model (Multiple Linear RegressionAnalysis). In accordance with the results of this study, it can be concluded several things including: The factors of organizational culture and organizational climate have a real influence simultaneously (together) on employee job satisfaction of Tandes Subdistrict, Surabaya City (Y), The factors of organizational culture and organizational climate have a real influence partially (individually) on employee job satisfaction of Tandes Subdistrict, Surabaya City (Y), Among the factors of organizational culture and organizational climate, it turns out that organizational climate has a dominant influence on employee job satisfaction of Tandes Subdistrict, Surabaya City (Y), with a partial influence of 63.8%. Constructive input suggestions, which we can contribute to the progress of the agency, namely in accordance with the wishes of the central government, in this case the President of the Republic of Indonesia, so that the government provides convenience in community services and investors, so that Indonesia's economic growth accelerates amid the onslaught of the pandemic and the war crisis in Europe, it is necessary to strive for increasingly high-quality and high-performance community services.